Carbono almacenado en la biomasa de las plantaciones forestales de Simarouba amara "marupa" y de Cedrelinga cateniformes Ducke "tornillo" del CIEFOR Puerto Almendra, Loreto-Perú 2021 - Guzmán Lozano, Jossie Madelen (2023)
The study allows evaluating its structure and assessing the impact on the mitigation of greenhouse gases and aims to estimate the biomass and carbon stored in forest plantations of Simarouba amara "marupa" and Cedrelinga cateniformes Ducke "tornillo" of CIEFOR, Puerto Almendra, Faculty of Forestry Sciences of the National University of the Peruvian Amazon. The plantations of S. amara "marupa", those of 43 years old have an average of 0.24 m of DBH and a height of 18.90 m; of 27 years old have an average of 0.23 m of DBH and a height of 22.49 m and of 34 years old have an average of 0.26 m of DBH and a height of 18.86 m. The plantation of C. cateniformes Ducke "tornillo", 15 years old has an average of 0.29 m DBH and a height of 26.11 m; 43 years old has an average of 0.51 m DBH and a height of 24.89 m and 35 years old has an average of 0.45 m DBH and a height of 28.74 m. The biomass present in the plantation of S. amara of 43 years with 53.80 kg; of 27 years with 76.33 kg and of 34 years with 68.06 kg and in the plantation of C. cateniformes Ducke, of 35 years has 476.79 kg; of 15 years with 106.03 kg and of 43 years with 656.65 kg. The carbon stored in the S. amara plantation of 43 years with 0.027 tC; of 27 years with 0.038 tC and of 34 years with 0.034 tC and in the plantation of C. cateniformes Ducke of 35 years with 0.238 tC; of 15 years with 0.053 tC and that of 43 years with 0.328 tC. The statistical analysis shows that there is no age difference between biomass and total carbon in the plantation of S. amara "marupa" and there is a significant difference in the plantation of C. cateniformes Ducke.